Design, synthesis, and evaluation of novel 2-substituted 1,4-benzenediol library as antimicrobial agents against clinically relevant pathogens - Daiane Flores Dalla Lana; Bruna Gerardon Batista; Gabriella da Rosa Machado; Mário Lettieri Teixeira; Luís Flávio Souza de Oliveira; Michel Mansur Machado; Saulo Fernandes de Andrade; William Lopes; Marilene Henning Vainstein; Alejandro Peixoto de Abreu Lima; Enrique Pandolfi; Edilma Elayne Silva; et al. (Elsevier, 2019)
Development of new antimicrobial agents, capable of combating resistant and multidrug-resistant fungal and bacterial clinical strains, is necessary. This study presents the synthesis and antimicrobial screening of 42 2-substituted-1,4-benzenediols, being 10 novel compounds. In total, 23 compounds showed activity against fungi and/or bacteria. Benzenediol compounds 2, 5, 6, 8, 11, and 12 demonstrated broad spectrum antimicrobial actions, including resistant and multidrug-resistant species of dermatophytes (Trichophyton mentagrophytes), Candida spp. and the ESKAPE panel of bacteria. Minimum inhibitory concentrations of these compounds for fungi and bacterial strains ranged from 25 to 50 µg/ml and 8-128 µg/ml, respectively. The antifungal mechanism of action is related to the fungal cell wall of dermatophytes and membrane disruption to dermatophytes and yeasts, in the presence of compound 8. Specific structural changes, such as widespread thinning along the hyphae and yeast lysis, were observed by scanning electron microscopy. The effects of compound 8 on cell viability are dose-dependent; however they did not cause genotoxicity and mutagenicity in human leukocyte cells nor haemolysis. Moreover, the compounds were identified as nonirritant by the ex-vivo Hen's egg test-chorioallantoic membrane (HET-CAM). The furan-1,4-benzenediol compound 5 showed in vivo efficacy to combat S. aureus infection using embryonated chicken eggs. Therefore, the compounds 8, and 5 are promising as hits for the development of new antimicrobial drugs with reduced toxicity. Keywords: Fungi, ESKAPE pathogens, 1,4-benzenediol derivatives, Antimicrobial activity, Mechanism of action, Toxicity